Material characterization to assess effectiveness of surface treatment to prevent joint deterioration from oxychloride formation mechanism. (November 2019) - Wang, Xuhao; Sadati, Seyedhamed; Taylor, Peter; Li, Cheng; Wang, Xin; Sha, Aimin
Abstract: Joints in a rigid pavement can act as local reservoirs trapping deicing salts and moisture. Such a harsh micro-environment can impact the durability of sawn joint surfaces, resulting in premature distress even in cases where the bulk of pavement exhibits sufficient durability against frost action and chemical attack by deicing salts. A comprehensive experimental program was undertaken in this study to elucidate the mechanisms of deterioration of concrete exposed to de-icing salts. Plain cement paste samples cast with water-to-cement ratio of 0.40 were exposed to salt solutions prepared with 4% and 20% concentrations of CaCl2 and MgCl2 at 4 °C. A second series of paste specimens, treated with a wide range of sealers representing various generic types, were also exposed to the aforementioned salt solutions. Mechanisms of deterioration and formation of chemical compositions and phases were monitored at different exposure periods using X-ray diffraction (XRD), and differential scanning calorimetry (DSC). Moreover, concrete specimens were cast and treated with the same sealers to expand the fundamental observations from paste to concrete phase. Data obtained from plain cement paste specimens indicated no sign of calcium or magnesium oxychloride formation when exposed to 4% concentration of salt solutions, while oxychloride formation was detected at 20% concentrations. Potential for calcium oxychloride formation in sealed samples correlated well with paste expansion and visual concrete deterioration rates. Results indicated that an expansion threshold of 0.20 mm corresponded to the recommended threshold of oxychloride formation potential of 15 g per 100 g of paste (gOXY /gPaste ).